Benefit of Contrast-Enhanced PET/CT versus Non-Contrast-Enhanced PET/CT Relative to Lesion Detection, Lesion Characterization, and Diagnostic Accuracy in Patients with Cancer - Tanyaluck Thientunyakit (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND 2020 Objective: To investigate the benefit of contrast-enhanced PET/CT (PET/CECT) versus non-contrast-enhanced PET/CT (PET/ NCCT) relative to lesion detection, characterization, and diagnostic accuracy in cancer patients. Materials and Methods: The present study was a prospective study that included patients older than 18 years with histopathologically proven cancer who underwent [F-18] fluorodeoxyglucose ([F-18]FDG) PET/CT at the Division of Nuclear Medicine, Department of Radiology, Faculty of Medicine, Siriraj Hospital between December 2014 and November 2017. PET/ NCCT was performed followed by PET/CECT scan in all patients. The results of PET/NCCT, PET/CECT, and pre- and post-contrast enhanced PET/CT (PET/NCCT-CECT) for each patient were interpreted by one nuclear medicine physician and one radiologist. The sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) were calculated from ROC curve analysis. Results: One hundred ten patients were included. The mean age was 52.45±17.14 years, and 52.7% were female. Lymphoma was the most common cancer diagnosis (47.3%). No significant difference was observed between PET/CT techniques for detection rate at the primary tumor site, lymph node, or distant organ. High agreement was observed between PET/CT techniques for lesion characterization. Lesion characterizations were not significantly correlated with age, gender, BMI, or FBS; however, lesion characterization was found to be significantly associated with primary tumor site, indication for PET/CT and lesion size. The following ranges were observed from all PET/CT techniques: sensitivity 81.5% to 85.3%, specificity 94.4% to 95.5%, accuracy 89.4% to 91.4%, PPV 90.4% to 92.1%, and NPV 88.9% to 91.3%. Conclusion: [F-18]FDG PET/CECT demonstrated no significant advantage over PET/NCCT for lesion detection, lesion characterization, or diagnostic accuracy in patients with cancer. The use of intravenous contrast material should be limited to select cases to reduce the risk of renal toxicity or anaphylactic reaction, and to minimize unnecessary costs.